2020
DOI: 10.1039/d0cc00472c
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of 3D colon cancer stem cell spheroids by cytotoxic RuII-p-cymene complexes of mesalazine derivatives

Abstract: RuII-p-cymene complexes of imidazole–mesalazine based ligands kill bulk and stem colon cancer cells with tight regulation over stemness markers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
23
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 17 publications
(26 citation statements)
references
References 34 publications
3
23
0
Order By: Relevance
“…We have synthesized and characterized a series of N,O and N,Ncoordinated Ru II complexes (1-9) with ligands having 3-aminobenzoate forming Schiff bases with five different aldehydes. Similar to our earlier reports, [65] the pyridine based N,Ncoordinated complexes are less stable, more hydrophilic and less cytotoxic (1)(2)(3)(4). The presence of a pendant free carboxylic acid group also decreased cytotoxicity ( 1 and 4).…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…We have synthesized and characterized a series of N,O and N,Ncoordinated Ru II complexes (1-9) with ligands having 3-aminobenzoate forming Schiff bases with five different aldehydes. Similar to our earlier reports, [65] the pyridine based N,Ncoordinated complexes are less stable, more hydrophilic and less cytotoxic (1)(2)(3)(4). The presence of a pendant free carboxylic acid group also decreased cytotoxicity ( 1 and 4).…”
Section: Discussionsupporting
confidence: 88%
“…The complexes, with the free À COOH groups, 1 and 4, were ineffective, which may be ascribed to their poor solution stability and low pK a of free acid groups making them difficult to traverse the cell membranes at the physiological pH of 7.4. [65] It may be argued that 1 has PF 6…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The complexes were synthesized according to a procedure similar to that reported by us earlier. 30 Precisely, a methanolic solution of [Ru II (p-cymene)(Cl) 2 ] 2 (30.5 mg, 0.05 mmol) or [Ru II (p-cymene)(I) 2 ] 2 (49 mg, 0.05 mmol) was added to a methanolic solution of the respective ligands (0.1 mmol) in the dark under a nitrogen atmosphere and stirred for 24 h. NH 4 PF 6 (0.15 mmol) was then added and the solution stirred for another 30 min. The solvent from the resultant mixture was evaporated under reduced pressure, and the yellow solid obtained was dissolved in cold dichloromethane and filtered to remove any excess NH 4 PF 6 .…”
Section: ■ Experimental Sectionmentioning
confidence: 99%
“…P-cymene is an extract of Eupatorium, which is the most important active ingredient and has antioxidant and antitumoral activity potentials [8][9]. Acharya et al [10] found that P-cymene can inhibited the viability and size of the HT-29 colonospheres in 3D colon cancer stem cells pheroids and do not enhance the expression of HES-1 gene, a crucial downstream gene in the Notch signalling…”
Section: Introductionmentioning
confidence: 99%